Particle-Antiparticle Asymmetry from Magnetogenesis Through the Landau Mechanism - Gamboa-Rios, J (2013)
Motivated by string theory an extension of the Landau problem to quantum field theory is considered. We show that the commutator between momenta of the fields violates Lorentz and CPT invariance leading to an alternative method of understanding the question of particle-antiparticle asymmetry. The presence of magnetic field at very early moments of the universe would then suggest that the particle-antiparticle asymmetry can be understood as a consequence of magnetogenesis. © 2012 Elsevier B.V.